Prevalensi anemia defisiensi besi pada tenaga kesehatan di Ruang Layanan Infeksi COVID-19 RSUD Sekayu, Kabupaten Musi Banyuasin - Erty Sundarita; Mediarty; Ghanie, Ali; Reagan, Muhammad; Putra, Ahmad Khoirun; Istiqomah, Amelia; Haryadi, Muhammad; Zetira, Rizha; Puspalina, Ferda; Hermawan, Nandi (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2021)
Anemia is a medical problem that occurs throughout the world, especially in developing countries such as Indonesia. One type of anemia that is often asymptomatic (silent anemia) is iron deficiency anemia, which mostly occurs in the productive age group. This condition in addition to causing a decrease in work productivity also affects the body's immunity which is very important in the current state of the COVID-19 pandemic. The purpose of this activity was to determine the pattern of anemia and the prevalence of iron deficiency anemia in health workers who work in the COVID-19 infection service room who are at high risk for infection if they have a weak immune system. The results showed that 11 people (14.47%) of health workers had absolute or relative iron deficiency anemia. Although this figure is relatively lower than the national average, the management of this condition is very important because it is related to the services that will be provided to the community.